INITIAL SCREENING OF FAST-GROWING TREE SPECIES BEING TOLERANT OF DRY TROPICAL PEATLANDS IN CENTRAL KALIMANTAN, INDONESIA - Saito, Hideyuki; Shibuya, Masato; Tuah, Sehat Jaya; Turjaman, Maman; Takahashi, Kunihide; Jamal, Yahya; Segah, Hendrik; Putir, Patricia Erosa; Limin, Suwido Hester (Indonesian Journal of Forestry Research, 2005)
An investigation of the recruit, survivorship and growth of naturally regenerating tree species on canal bank was conducted to  select tree species which are suitable for preceding planting in drained and burnt peat swamp lands in  Central Kalimantan, Indonesia.  Top of  the canal bank were open, with greater soil moisture  deficit and higher soil temperatures than on the next intact forest floor. The abundant  trees were asam-asam (Ploiarium alternifolium),garunggang (Cratoxylon arborescens) and tumih (Combretocarpus rotundatus). New regeneration of these trees on the canal bank was confirmed during this investigation and mortality was very low. These results indicated that P. alternifolium,C. arborescens and C. rotundatuswere tolerant of intensive radiation, soil drought and high soil temperatures during germination. The annual height increments  were 189-232  cm y-1 (P. alternifolium),118-289  cm y-1  (C. arborescens)and 27-255 cm y-1   (C. rotundatus); thus, these three species could be classified as fast-growing with tolerance to open and dry conditions.  Such characteristics were important to avoid competition with herbs, ferns,and/ or climbers. The results·suggest that P.alternifolium,C. arborescens and C. rotundatusare suitable for preceding planting for the rehabilitation of the disturbed peat swamp forests of Central Kalimantan.